An Assessment of the Traumatic Experiences of Women Victims of Boko Haram Insurgency in Michika - Roseline Luka Vandi; Ikenye Ndung'u; Julius Kithinji (Eastern African Journal of Humanities and Social Sciences)
Terrorism in the twenty-first century is a significant cause of global trauma. It has hit almost every nation, with Nigeria being adversely affected by the rise of the Boko Haram insurgency, more prevalent in the North-Eastern part of the country. Michika, the local government of Adamawa State, is one such place that has been destabilised economically, socially, spiritually, and structurally. Women have been traumatised because they are a significant target. This paper assesses the traumatic experiences of women victims of the Boko Haram insurgency in Michika. The article further delineates the role of the church, government, and other relevant stakeholders in response to the plight of women. The study adopted a qualitative approach, collecting data through interviews, focused group discussions, and secondary sources. Data analysis was then done thematically. It was established that women experienced the insurgency differently than men because they were targets for sexual exploitation, sex slavery, forced marriage, and conscription. Their businesses and other sources of livelihood have been affected, thus leaving them in abject poverty, a situation that only little can be accomplished by the government, church, and other organisations' sporadic interventions. More so, a single approach to counseling will fall short of addressing the issues and reintegrating them into society. Therefore, this paper recommends that the church should reposition itself to facilitate collaborative efforts in providing a long-lasting intervention that seeks to heal, empower, and reintegrate women into society so they can live everyday lives again.